Profile of Students Resilience and Implications of Guidance and Counseling - Pribadi, Pribadi; L.N, Syamsu Yusuf; Yustiana, Yusi Riksa (Universitas Muhammadiyah Metro, 2018)
This study aims to obtain a profile of adolescent resilience in grade VIII level of junior high school students. This research uses a descriptive quantitative method. The study was conducted on students of class VIII SMP Negeri 3 Cimahi 2017/2018 academic year with the total population is 452 students, and the number of research samples is 443 students. The instrument used in this study was adapted and modified from the resilience theory in Bonnie Benard's' book